Vietnam : On the Road to Labor-Intensive Growth? - Belser, Patrick (World Bank, Washington, DC, 2015)
Since Vietnam's adoption of the doi moi or renovation policy in 1986, the country has been undergoing the transition from central planning to a socialist market-oriented economy. This has translated into strong economic growth, led by the industrial sector, which expanded more than 13 percent a year from 1993 to 1997. Vietnamese policymakers are concerned, however, that employment growth has lagged. To address this concern, the author compares new employment data from the Vietnam Living Standards Survey (VLSS 2), completed in 1997-98, with data from the first household survey undertaken in 1992-93. He shows that in 1993-97, industrial employment grew an average of about 4 percent a year, which is low compared with industrial GDP growth. This slower growth was attributable to the capital-intensive, import-substituting nature of the state sector and foreign investment, which dominate industry. The more labor-intensive, export-oriented domestic private sector is still small, although growing quickly. In the future, growth promises to become more labor-intensive. Before the Asian crisis there were signs of an emerging export-oriented sector. Using previous statistical analysis (Wood and Mayer 1998) as well as factor content calculations, the author estimates that given Vietnam's endowment of natural and human resources, Vietnam could triple its manufacturing exports and create about 1.6 million manufacturing jobs in export sectors in the near future. After examining Vietnam's labor regulations, the author concludes that there is no need for basic reform of the labor market. At current levels, minimum wages and nonwage regulations (even if better enforced) are unlikely to inhibit development of the private sector or hurt export competitiveness. But a restrictive interpretation of the Labor Code's provisions on terminating employment could hurt foreign investment, reduce the speed of reform in the state sector, and slow the reallocation of resources to the domestic private sector.